2019
DOI: 10.1177/2055217319888660
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a consumer-grade activity monitor for continuous daily activity monitoring in individuals with multiple sclerosis

Abstract: Background: Technological advancements of remote-monitoring used in clinical-care and research require validation of model updates. Objectives: To compare the output of a newer consumer-grade accelerometer to a previous model in people with multiple sclerosis (MS) and to the ActiGraph, a waist-worn device widely used in MS research. Methods: Thirty-one individuals with MS participated in a 7-day validation by the Fitbit Flex (Flex), Fitbit Flex-2 (Flex2) and ActiGraph GT3X. Primary outcome was step count. Vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Digital Patient Generated Health Data (PGHD), a recently introduced technology, has become available with the widespread availability of digital mobile devices, and can potentially fill the information gaps left by conventional sources of real-world data 14,15 . Wearable devices in particular that track physical activities or physiologic parameters like heart rate allow for the passive inference of behavioral activity patterns with time granularities not possible with conventional RWD [16][17][18] . Though still in the early stages of widespread clinical use, PGHD could potentially be used to gain more nuanced data on patient centered outcomes, and serve as passive health diaries with information to guide medication approaches personalized to the individual user 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Digital Patient Generated Health Data (PGHD), a recently introduced technology, has become available with the widespread availability of digital mobile devices, and can potentially fill the information gaps left by conventional sources of real-world data 14,15 . Wearable devices in particular that track physical activities or physiologic parameters like heart rate allow for the passive inference of behavioral activity patterns with time granularities not possible with conventional RWD [16][17][18] . Though still in the early stages of widespread clinical use, PGHD could potentially be used to gain more nuanced data on patient centered outcomes, and serve as passive health diaries with information to guide medication approaches personalized to the individual user 19 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 27 ] Another study that compared average step counts per day, this time looking at Fitbit Flex and Fitbit Flex 2 estimates for people with MS to a research-grade AG GT 3 X+, found that both of the consumer WPAM overestimated steps per day. The Fitbit Flex overestimated an average of 873 steps per day while the Fitbit Flex 2 overestimated 808 steps per day with the magnitude of overestimation for both monitors increasing for individuals with higher Expanded Disability Status Scale scores [ 28 ]. This study also compared total step counts from the Fitbit Flex to directly observed hand-tallied step counts during a 2-minute walk test and found no systematic bias.…”
Section: Discussionmentioning
confidence: 99%
“…55 Furthermore, activity trackers are normally worn on the wrist. [56][57][58] Conversely, smartphones and wearable activity trackers are not usually attached to the waist, 16 59-61 hip 62 63 and chest, 17 as was observed in several validation studies. Importantly, it has been shown that step counting error is impacted by wear location, with hip-based devices demonstrating a higher accuracy than wrist-worn devices, 64 while smartphone accuracy changes based on the device, location (waist, arm, hand or bag) and nature of the activity (running or walking).…”
Section: Index Measurementioning
confidence: 99%